(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Since mathematics is the universal language of science and technology, it has played a key role in many breakthroughs that have transformed contemporary civilisation. Mathematics offers the fundamental skills for comprehending, modelling, and solving complicated issues, from the discovery of far-off galaxies to the encryption techniques that safeguard our digital world. This study examines mathematics’ significant contributions to a variety of fields, emphasising how mathematics has aided in the advancement of contemporary scientific and technical advancements.